Impact of Virtual Classes on University Students During Covid-19 - Armijos, Juan Carlos (2023)
The global pandemic, caused by Covid-19, has significantly exacerbated the problems of various sectors of our society, with higher education being one of the most widely affected sectors; To deal with this situation, an “emergent adjustment” had to be made, replacing face-to-face classes with virtual semesters and periods. Objective: To investigate and know the perception of the students of the Santo Tomás Chile University, regarding their experiences in virtual classes during the year 2021, and their perspective regarding the return to face-to-face classes. Methodology: Survey applied to university students combining a mixed approach of both quantitative and qualitative aspects. Results: Most of the students have technological devices for the development of virtual classes. About this experience, the students have had shared visions between center options, although satisfaction prevailed. The level of demand was high. Among the main drawbacks were connectivity problems, lack of adequate space in the home, and distraction from the family environment. Conclusions: The response capacity to give continuity to the school year stands out, an uncertain level of educational quality to measure, and the presence of practices and technological elements that could be used in the future.